2007
DOI: 10.1659/0276-4741(2007)27[48:lualcc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Land Use and Land Cover Change in Highland Temperate Forests in the Izta-Popo National Park, Central Mexico

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 32 publications
0
24
0
3
Order By: Relevance
“…In fact, the most diverse populations, which were historically source populations, are found in the eastern part of the range and are not currently protected. The north‐eastern highlands of the TVB are threatened by severe encroachment due to urban and agricultural development (García‐Romero, 2002; Galicia & García‐Romero, 2007). The preservation of populations with high genetic diversity is especially important for preserving adaptive genetic variation and evolutionary potential in the face of global environmental change (Spielman et al.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the most diverse populations, which were historically source populations, are found in the eastern part of the range and are not currently protected. The north‐eastern highlands of the TVB are threatened by severe encroachment due to urban and agricultural development (García‐Romero, 2002; Galicia & García‐Romero, 2007). The preservation of populations with high genetic diversity is especially important for preserving adaptive genetic variation and evolutionary potential in the face of global environmental change (Spielman et al.…”
Section: Discussionmentioning
confidence: 99%
“…In central Mexico, some Quercus forests (dominated by Quercus deserticola and Quercus frutex among others) are often associated with water-stress conditions similar to those found in scrubs (Medina Lemus and Tejero-Díez 2006). Also, severe deforestation in the last century in central Mexico has led to the establishment of shrub-or scrub-type vegetation in sites previously occupied by Quercus or other tree species (Rzedowski 1978;Challenger 1998;Galicia and García-Romero 2007). In particular, in one scrub locality sampled in this study (Concordia), we found several sparsely Quercus sp.…”
Section: Differential Morphological Expression Of C Bipinnatus Undermentioning
confidence: 50%
“…TMF temperate montane forest, MCF montane cloud forest, TRF tropical rain forest, TSDF tropical semideciduos forest of the Yucatán peninsula, TDF tropical dry forests along the Pacific Coast of Mexico, CHD chihuahuan desert, CRP coral reefs, Pacific, CRC coral reefs, Caribbean, MF mangrove forest, KF kelp forest, SLE saline lake ecosystems c ecosystem (Table S1). These forests are characterized by slower rates of recovery where land use conversion to agriculture and forestry are considered the major anthropogenic disturbance (Galicia and García-Romero 2007). Infrastructure development near this ecosystem can influence greater areas.…”
Section: Terrestrial Ecosystemsmentioning
confidence: 99%